Analisis Proses Produksi Program Siaran Berita Padang Pagi Ini Di Pro 1 - Sari Zai, Jubaida; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This thesis is entitled "Analysis of the Production Process of Padang Pagi Ini News Broadcast Program at Pro 1 Radio Republik Indonesia Padang". The purpose of this research is to find out the production process of the news broadcast program "Padang Pagi Ini" at Pro 1 RRI Padang and to find out the factors that influence the production process of the news broadcast "Padang Pagi Ini" at Pro 1 RRI Padang. This research uses descriptive qualitative research methods. As a qualitative descriptive researcher, the researcher will only describe the situation or event, not looking for relationships, not testing hypotheses or making predictions. the results showed that the stages of the production process of "Padang Pagi Ini" are the same as the production process of radio programs in general, including: pre-production stages, production stages, post-production stages and factors affecting news production at RRI Padang are human resources, technology, content management, broadcasting regulations, and audience feedback. The production team consists of journalists, reporters, producers, editors, and technicians who have competencies and experience that affect the quality of the news presented. Technology such as digital cameras, video editing software and digital transmission systems facilitate the news production process.